2021
DOI: 10.1038/s42003-021-02878-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of hydropower on the habitat of jaguars and tigers

Abstract: The rapid expansion of hydropower across tropical landscapes has caused extensive habitat loss and degradation, triggering biodiversity loss. Despite known risks to freshwater biodiversity, the flooding of terrestrial habitats caused by dam construction, and associated impacts on terrestrial biota, have been rarely considered. To help fill this knowledge gap, we quantified the habitat loss following inundation of hydropower reservoirs across the range of two iconic species, jaguars and tigers. To do so, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“… Aquatic ecosystem entropy — In general, the installation and operation of water-based energy systems, in the long run, instigate various degrees of entropy in the ecosystem. Typical perturbations experienced include turbine injuries sustained by aquatic life and wildlife, increased sedimentation, nutrient, chemical and toxic metal leakage and accumulation, algal bloom and eutrophication, habitat fragmentation that causes changes in migratory patterns of fishes and wildlife (Palmeirim and Gibson 2021 ; Baird et al 2021 ), constrained reproduction in certain fish species, as well as exposure of other aquatic fauna to intense predation. In some cases, considerable amounts of CO 2 and CH 4 emissions might occur alongside the decline in dissolved oxygen.…”
Section: A Well-balanced Succinct Appraisal Of Some Existing New Gene...mentioning
confidence: 99%
“… Aquatic ecosystem entropy — In general, the installation and operation of water-based energy systems, in the long run, instigate various degrees of entropy in the ecosystem. Typical perturbations experienced include turbine injuries sustained by aquatic life and wildlife, increased sedimentation, nutrient, chemical and toxic metal leakage and accumulation, algal bloom and eutrophication, habitat fragmentation that causes changes in migratory patterns of fishes and wildlife (Palmeirim and Gibson 2021 ; Baird et al 2021 ), constrained reproduction in certain fish species, as well as exposure of other aquatic fauna to intense predation. In some cases, considerable amounts of CO 2 and CH 4 emissions might occur alongside the decline in dissolved oxygen.…”
Section: A Well-balanced Succinct Appraisal Of Some Existing New Gene...mentioning
confidence: 99%
“…Anthropogenic variables were often described as significant groups of variables negatively affecting jaguar presence as a result of human infrastructure, population growth, and human behaviors (e.g., Silveira et al 2014;Montanarin 2020;Palmeirim and Gibson 2021). Within subcategories, 28-53% of studies including such variables reported at least one as important affecting jaguar distribution (Table 2).…”
Section: Anthropogenic Variablesmentioning
confidence: 99%
“…86 Hydroelectric dams cause, among others, deforestation and loss of natural ecosystems and biodiversity (goal 15), they can reduce water quality and quantity eliminating fish species, aquatic organisms and nesting areas of turtles (goal 14) 87,88 and they can impact the habitat of animals, such as jaguars and tigers. 89 Despite such conflicts, renewable energy projects, implemented within the framework of the Sustainable Development Agenda, continue due to the anthropocentric focus of policy-makers. With the targets of goals 14 and goal 15 emphasising the protection of aquatic and terrestrial ecosystems, the specific rights and welfare situation of individual animals or animal species are very often neglected in such analyses of SDG trade-offs or in decision-making on SDG projects.…”
Section: Trade-offs In Animal Rights and Animal Welfarementioning
confidence: 99%
“…First studies, however, reveal that individual animals as well as species are severely affected by renewable energy endeavours. 90,91 As animals are sentient beings and key components of functioning ecosystems, these impacts on animals need to be much more seriously considered, analysed and prevented to achieve environmental sustainability. Without these considerations, and a shift from anthropocentric to ecocentric decision-making, the SDG agenda will neither be transformative nor sustainable.…”
Section: Trade-offs In Animal Rights and Animal Welfarementioning
confidence: 99%